How mathematics teachers' special knowledge changing: A case study in the Professional Teacher Education program - Matitaputty, Christi; Nusantara, Toto; Hidayanto, Erry; Sukoriyanto (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The COVID-19 pandemic has catalyzed the widespread adoption of distance learning, necessitating a comprehensive understanding of how teacher knowledge evolves within the context of Teacher Professional Education (TPE) programs. Some research endeavors may employ evaluation methodologies that inadequately capture the nuanced dimensions of knowledge, highlighting the necessity for greater incorporation of evidence-based approaches in the formulation and assessment of teacher development initiatives. This study employs a qualitative methodology to explore the evolution of Mathematics Teachers' Specialized Knowledge (MTSK) within the framework of a TPE program. Data were gathered through the engagement of three educators in the preparation and execution of lessons on permutation and combination via a Learning Management System (LMS), coupled with in-depth interviews. The findings underscore the TPE program's role in fostering collaborative learning environments through participation in online educational communities. Teachers are shown to be increasingly integrating technology into their pedagogical practices, albeit with varying degrees of proficiency. The presence of Professional Learning Communities (PLCs) is identified as instrumental in supporting educators in refining instructional strategies to enhance teaching effectiveness. Nevertheless, there remains a subset of teachers necessitating more profound and more comprehensive content knowledge about their subject matter. These insights emphasize the importance of designing TPE programs that offer sustained and adaptable professional development opportunities to facilitate continuous growth among educators. Consequently, it is recommended that online learning communities geared toward addressing the diverse learning requirements of students be established, thereby aiding in the identification and resolution of pedagogical challenges.